Predictors of suicide attempts among adolescents with suicidal ideations and a plan: Results from the National Survey on Drug use and Health (NSDUH) - Michele Cherro; Hala Itani; Elias Ghossoub; Fadi Maalouf (PLoS ONE, 2025)
Purpose Suicide remains an ongoing public health concern, especially among adolescents. While many studies investigated the transition from ideations to attempts, they did not specifically look at the factors underlying the transition from a suicide plan to a suicide attempt, creating a vast knowledge gap. In the following study, we aim to investigate predictors of suicide attempts among adolescents with a suicide plan using data from NSDUH. Methods We used de-identified data from consecutive cross-sectional NSDUH surveys conducted between 2015 and 2018, including respondents aged 12–17 who reported suicidal ideations and a plan. We performed bivariate analyses and multivariate logistic regression analyses to identify significant predictors of suicide attempts in our population. Results Our total sample included 3003 respondents (Population Size Estimate: 1,284,704.48). Among them, 1,780 reported suicide attempts (A) and 1,223 reported no suicide attempts (NA). The majority of adolescents in both groups were aged 15–17 years. More females were present in the (A) group compared to the (NA) group (p = 0.013). We found a positive association between antisocial behaviors and suicide attempts. Specifically, engaging in three or more antisocial behaviors significantly increased the odds of suicide attempts [adjusted odds ratio (OR) = 1.81; 95% CI = (1.11–2.96). Substance use and violent behaviors were also significantly associated with an increased suicide risk. Conclusion We found significant correlations between suicide attempts and gender, substance use disorders and engaging in antisocial behaviors. These findings underscore the importance of addressing mental health issues, substance use, and antisocial behaviors in suicide prevention efforts for at-risk adolescents.